Do thermal tolerances and rapid thermal responses contribute to the invasion potential of Bactrocera dorsalis (Diptera: Tephritidae)?. (April 2017) - Pieterse, Welma; Terblanche, John S.; Addison, Pia
Graphical abstract: Both C. capitata and C. rosa cold hardened, B. dorsalis did not. Ceratitis capitata heat hardened greatly compared to C. rosa and B. dorsalis . B. dorsalis has a smaller thermal niche than other invasive Tephritidae. Abstract: Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) has shown remarkable range expansion over the past 10 years and invaded several new continents including Africa. Here we report results of a detailed assessment of acute high and low temperature survival ability and the plasticity thereof, to test the hypothesis that traits of the thermal niche have contributed to the species' invasion ability. We also assess life-stage-related variation of thermal tolerances to determine potential stage-related environmental sensitivity. The temperatures at which c . 20% of the population survived of B. dorsalis were determined to be −6.5 °C and 42.7 °C, respectively, when using 2 h exposures. Further, four life stages of B. dorsalis (egg, 3rd instar larvae, pupae and adults) were exposed to high and low discriminating temperatures to compare their thermal survival rates. The egg stage was found to be the most resistant life stage to both high and low temperatures, since 44 ± 2.3% survived the low and 60 ± 4.2% survived the high discriminating temperature treatments respectively. Finally, the potential for adult hardening responses to mediate tolerance of extremes was also considered using a diverse range of acute conditions (using 2 h exposures to 15 °C, 10 °C and 5 °C and 30 °C, 35 °C, 37 °C and 39 °C as hardening temperatures, and some treatments with and without recovery periods between hardening and discriminating temperature treatment). These showed that although some significant hardening responses could be detected in certain treatments (e.g. after exposure to 37 °C and 39 °C), the magnitude of this plasticity was generally low compared to two other wide-spread and more geographically-range-restricted con-familial species, Ceratitis capitata and C. rosa . In other words, Bactrocera dorsalis adults were unable to rapidly heat- or cold-harden to the same extent as the other Ceratitis species examined to date. These results suggest a narrower thermal niche in B. dorsalis compared to these Ceratitis species – in both basal and plastic terms – and suggests that its geographic distribution might be more restricted in consequence.